The Imprisonment of Indigenous Student Identities Within Educational Organizations: A Personal Journey - Carrie Whitlow (Adult Education Research Conference, 2022)
In this article, I analyze my experience as an Indigenous student in an all-white public school system to a Tribal College and University (TCU), specifically exploring the transition period from a senior in high school to a freshman in college.
Keywords: Indigenous Autoethnography; Tribal Critical Theory (TribalCrit); Tribal College and University (TCU)